Lung function in a cohort of 5‐year‐old children born very preterm. Issue 12 (21st October 2018) - Lombardi, Enrico; Fainardi, Valentina; Calogero, Claudia; Puglia, Monia; Voller, Fabio; Cuttini, Marina; Rusconi, Franca
Abstract: Objective: We assessed lung function and respiratory health in an area‐based prospective cohort of preschool children born very preterm. Design: Lung function was measured by interrupter respiratory resistance (Rint) and forced oscillation technique (FOT) (respiratory resistance (Rrs8), reactance (Xrs8), and area under the reactance curve (AX)) at a median age of 5.2 years in a cohort of 194 children born at 22‐31 weeks of gestational age (GA) in Tuscany, Italy. Respiratory symptoms and hospitalizations were also assessed. Results: Mean (SD) lung function Z‐scores were impaired in preterm children for Rint (0.72 (1.13)), Xrs8 (‐0.28 (1.34)), and AX (0.29 (1.41)). However, only a relatively small proportion of children (14.5‐17.4%) had values beyond the 95th centile or below the 5th. Children with bronchopulmonary dysplasia (BPD) ( n  = 24) had slightly but not significantly impaired lung function indices in comparison with those without BPD ( n  = 170). In a multivariable analysis, lower GA was associated with worse lung function indices. Fifty‐five percent of children had a history of wheezing ever and 21% had been hospitalized in their lifetime because of lower respiratory infections; 31% had wheezing in the last 12 months and this was associated with increased Rrs8 ( P  = 0.04) and AX ( P  = 0.08), and with decreased Xrs8 ( P  = 0.04) Z‐scores. Conclusions: Irrespectively of BPD preschool children born very preterm had impaired lung function indices, as measured by Rint and FOT, and a slightly higher burden of respiratory problems than the general population. GA seems to be crucial for lung development.